Predictors of aneurysm obliteration in patients treated with the WEB device: results of a multicenter retrospective study - Mastorakos, Panagiotis; Möhlenbruch, Markus Alfred; Ulfert, Christian (American journal of neuroradiology, 2024)
BACKGROUND AND PURPOSE: Despite the numerous studies evaluating the occlusion rates of aneurysms following WEB embolization, there are limited studies identifying predictors of occlusion. Our purpose was to identify predictors of aneurysm occlusion and the need for retreatment. - MATERIALS AND METHODS: This is a review of a prospectively maintained database across 30 academic institutions. We included patients with previously untreated cerebral aneurysms embolized using the WEB who had available intraprocedural data and long-term follow-up. - RESULTS: We studied 763 patients with a mean age of 59.9 (SD, 11.7) years. Complete aneurysm occlusion was observed in 212/726 (29.2%) cases, and contrast stasis was observed in 485/537 (90.3%) of nonoccluded aneurysms. At the final follow-up, complete occlusion was achieved in 497/763 (65.1%) patients, and retreatment was required for 56/763 (7.3%) patients. On multivariable analysis, history of smoking, maximal aneurysm diameter, and the presence of an aneurysm wall branch were negative predictors of complete occlusion (OR, 0.5, 0.8, and 0.4, respectively). Maximal aneurysm diameter, the presence of an aneurysm wall branch, posterior circulation location, and male sex increase the chances of retreatment (OR, 1.2, 3.8, 3.0, and 2.3 respectively). Intraprocedural occlusion resulted in a 3-fold increase in the long-term occlusion rate and a 5-fold decrease in the retreatment rate (P < .001), offering a specificity of 87% and a positive predictive value of 85% for long-term occlusion. - CONCLUSIONS: Intraprocedural occlusion can be used to predict the chance of long-term aneurysm occlusion and the need for retreatment after embolization with a WEB device. Smoking, aneurysm size, and the presence of an aneurysm wall branch are associated with decreased chances of successful treatment.
Gesehen am 28.04.2025